Turn Your Attention to Distractions. Issue 3 (24th September 2022) - Rothman, B.S.; Bledsoe, S.; Rice, M.J.
Abstract : ( Anesth Analg . 2022;134:266–268) The use of personal electronic devices (PEDs) in health care can support effective communication, enhance patient safety and contribute to higher quality of care. PEDs allow providers to document care in electronic medical records, communicate securely, and leverage applications for situational awareness. They can also be used to support medical education and direction, as well as care team models, regardless of location.